Analysis of the Rhetoric in the First President's Speech Prabowo Subianto at the Inauguration Ceremony President of 2024 - Ukhti Jelita; Andy Corry; Nina Yudha Aryanti; Nanang Trenggono; Nanda Utaridah (SAINTIS Publishing, 2025)
The purpose of this study is to ascertain the rhetoric used in President Prabowo Subianto's 2024 inaugural speech. Using a constructivist paradigm, this study employs a qualitative approach and analyzes the five laws of rhetoric as proposed by Aristotle and the classical rhetoricians (Socrates, Plato, and Demosthenes). President Prabowo Subianto is the focus of this study, and the video of his 2024 inauguration speech serves as the target of the study. A fill-in system is used to analyze the data. The findings of this investigation are (1) The speech's topic was sustainable development and economic prosperity, with an emphasis on renewable energy and sustainable agriculture to preserve natural resources, economic growth and environmental sustainability, building a robust economy with jobs for all, enhancing infrastructure, assisting small and medium-sized businesses, and boosting competitiveness in the global market. (2) Disposition (drafting) in the form of an introduction that includes content, arguments, proof, and greetings. (3) Elocutio (style of language) Proverbs, metaphors, and repetition are the language style employed. (4) Recollections (memory) President Prabowo Subianto described his experiences in a speech without consulting the text. (5) President Prabowo Subianto emphasized, lowered, and elevated vowels during his inauguration. He looked around, raised his hands halfway, and made pointing gestures. In order to persuade the audience, eye contact and mental interaction were employed. In conclusion, President Prabowo Subianto's speech complied with the theoretical requirements of classical rhetoricians and Aristotle's five laws of rhetoric, ensuring that the speech's rhetoric was understandable and focused on its goal.